Reflection on the Production of Knowledge: From Postmodernism to Pseudoscience - Daud Aris Tanudirjo (Humaniora, 2017)
In the last few years, the Indonesian government has impelled academics and higher education institutions as the centre of knowledge production to publish their works in reputed international journal. This policy is necessary to elevate the position of Indonesian higher education institution in the World University Rankings. In fact, such a policy will not only have impact on the status of the higher education institution but also in the course of human culture and society. This article tries to reflect on the impact of the implementation of the policy in the wider cultural context. Predictably, new knowledge will only be circulated among the elite academics and the higher education institutions will become inaccessible ivory tower for the society. On the other hand, the society will tend to consume more pseudoscientific knowledge which is more attractive and easier to understand. Ultimately this will have a significant impact on the course and quality of human culture.